Optimalisasi Good Governance melalui Prinsip Akuntabilitas Hukum dalam Pengelolaan Keuangan Negara - Anggraini, Mellisa (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This study discusses the importance of implementing the principle of accountability in state financial management to support the realization of good governance in Indonesia. The principle of results-oriented accountability emphasizes that every budget user must be responsible for the use of public funds and explain the performance of the organization, both in terms of the success and failure of a program. Although various regulations have been established to support transparent and accountable financial management, this study found that its implementation still faces challenges, such as lack of transparency, weak supervision, and slow law enforcement against violations. This study uses a normative legal approach to analyze how accountability can be implemented more effectively in state financial management to encourage the achievement of good governance. The results of the study indicate that increasing transparency, strengthening the internal supervision system, and stricter law enforcement are needed to create better governance in Indonesia.